The Role Of Management Practices On Academic Staff Performance In Private Universities In Uganda: A Case Of Bishop Stuart University - Birungi, Speciouza; Tukei, J. M. O.; Kazooba, Charles Tushabomwe; Mwesigye, Adrian Rwekaza (International Journal of Technology and Management, 2021)
Management practices relate to specific practices, formal policies and philosophies that are designed to attract, develop, motivate, and retain employees who ensure the effective functioning and survival of the organization. This paper examined the effects of management practices on staff performance in private universities. The study majorly employed a quantitative approach using a cross-sectional study design with some qualitative elements. 142 respondents were carefully chosen using different sampling techniques. Use of the survey, interviews focused group discussions together with documentary analysis were employed for both quantitative and qualitative approaches respectively. A total of 142 respondents played a part in the study. Data were analyzed using different statistical techniques that mainly included descriptive and inferential statistics respectively. Results were found to be statistically related to staff performance. For that matter, it was concluded that a number of elements of management practices were found to be influencing the performance of academic staff and these included recruitment and selection practices, compensation system (rewards incentives and penalties), employment security, training and development, use of information, performance appraisals, evaluating academic staff, development opportunities, and handling of performance misconduct. This is because these influenced academic staff’s professional conduct, promoted ethical standards and values, promoted organizational identity among staff and top management.
Keywords: Management Practices; Academic performance; Bishop Stuart University